2022
DOI: 10.3390/atmos13071103
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review of Cooling Center, Misting Station, Cool Pavement, and Cool Roof Intervention Evaluations

Abstract: Heat islands and warming temperatures are a growing global public health concern. Although cities are implementing cooling interventions, little is known about their efficacy. We conducted a literature review of field studies measuring the impact of urban cooling interventions, focusing on cooling centers, misting stations, cool pavements, and cool or green roofs. A total of 23 articles met the inclusion criteria. Studies of cooling centers measured the potential impact, based on evaluations of population prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…A large number of empirical studies and numerical simulations have demonstrated that vegetation generally has a regulating effect on human thermal comfort [18,24,70]. For example, in the residential area of Freiburg in southwestern Germany, Lee et al applied the ENVI-met model to simulate four different urban green coverage scenarios and noted a maximum reduction in PET of 17.4 K for trees on grasslands and only 4.9 K for grasslands [70].…”
Section: Human Thermal Comfort Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of empirical studies and numerical simulations have demonstrated that vegetation generally has a regulating effect on human thermal comfort [18,24,70]. For example, in the residential area of Freiburg in southwestern Germany, Lee et al applied the ENVI-met model to simulate four different urban green coverage scenarios and noted a maximum reduction in PET of 17.4 K for trees on grasslands and only 4.9 K for grasslands [70].…”
Section: Human Thermal Comfort Comparisonmentioning
confidence: 99%
“…At the same time, the negative impact of global climate issues included lower temperatures 2 of 21 in the cold season in some areas, and the proportion of deaths caused by cold was higher than that caused by heat [15]. In response to the problems caused by global climate change, mitigation and adaptation strategies, such as optimization of urban structure and increased use of reflective roofs and cool pavements, have been extensively explored [16][17][18][19]. Among these strategies, green spaces are seen as important resources for regulating the climate and microclimate [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, urban green infrastructures (UGI), building materials (for both road pavements and factories), public transport, water treatment, and urban ventilation are the key factors that affect an urban microclimate [16][17][18][19]. Therefore, the scientific literature is investigating the best strategies to counteract and mitigate the effects of UHIs [20][21][22]. For example, cool pavements can soften the negative effects of UHIs through different technologies [23][24][25].…”
Section: Introductionmentioning
confidence: 99%